2011
DOI: 10.1681/asn.2010010121
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Fas Ligand on Leukocytes Attenuates Kidney Ischemia-Reperfusion Injury

Abstract: Inflammation contributes to the pathogenesis of ischemic acute kidney injury (AKI), and T cells mediate the early phase of ischemia-reperfusion injury (IRI). The Fas/Fas ligand (FasL) pathway modulates the balance of T cell subsets in the peripheral circulation as well as multiple inflammatory responses, suggesting that FasL may mediate ischemic AKI. Here, we induced bilateral renal IRI in mice bearing a loss-of-function mutation of FasL (the gld mutation) and in wild-type mice. Compared with wild-type mice, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 42 publications
0
39
1
1
Order By: Relevance
“…TNF receptor 1/2 double-deficient mice are not protected from renal IRI, and interference with TNF does not protect mice from IRI (45). However, other members of the TNF superfamily have recently been implicated in the induction of necroptosis [e.g., TNF related apoptosis inducing ligand receptor (TRAIL-R) (46), Fas, or TWEAK] and are just as likely to be involved as members of the Toll-like receptors, some of which may trigger the intracellular RHIM-containing protein TRIF (TIR-domain-containing adapter-inducing interferon-β) (16).…”
Section: Discussionmentioning
confidence: 98%
“…TNF receptor 1/2 double-deficient mice are not protected from renal IRI, and interference with TNF does not protect mice from IRI (45). However, other members of the TNF superfamily have recently been implicated in the induction of necroptosis [e.g., TNF related apoptosis inducing ligand receptor (TRAIL-R) (46), Fas, or TWEAK] and are just as likely to be involved as members of the Toll-like receptors, some of which may trigger the intracellular RHIM-containing protein TRIF (TIR-domain-containing adapter-inducing interferon-β) (16).…”
Section: Discussionmentioning
confidence: 98%
“…These low numbers could reflect low sensitivity of this assay by flow cytometry, or this finding may suggest that although circulatory TNF-a plays a predominant role in mediating TNFR-dependent pulmonary apoptosis, T cell-dependent apoptosis occurs through an alternative death receptor pathway. For example, Fas ligand has been identified as a key mediator of renal injury, and FasL-deficient mice exhibited fewer infiltrating TNF-aproducing T lymphocytes in the kidney and renal lymph nodes (31). Alternatively, TNFR1 may be selectively upregulated in pulmonary ECs independent of T cell TNFR1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…22 It was reported that blockade of the Fas/FasL interaction attenuated IRI both in the kidney 23 and in the liver. 24 So we isolated thymocytes, liver mononuclear cells (MNCs) and splenocytes, which were subjected to flow cytometry analyses.…”
Section: Hif-2a Knockout Led To Upregulated Fasl Expression On Periphmentioning
confidence: 99%
“…FasL blockade was implemented by in vivo administration of a functional-grade purified anti-mouse FasL antibody, as previously described. 23 Anti-FasL Ab (16-5911; eBioscience) or control hamster IgG (control Ab) were injected intraperitoneally (500 mg per mouse) at 24 hours before IR insult, and a booster injection at half dose was administered immediately after the initiation of reperfusion.…”
Section: Nk11 + Cell Depletion and Fasl Blockadementioning
confidence: 99%